2007
DOI: 10.1108/14777270710828900
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum fetal monitoring and the spectre of litigation

Abstract: Purpose -The routine use of intrapartum electronic fetal monitoring (EFM) has resulted in an increased burden of operative and vaginal instrumental deliveries for women at low obstetric risk. Such modes of delivery increase maternal mortality and morbidity risks. This study aims to explore midwives' values, attitudes and beliefs when using intrapartum fetal monitoring techniques in clinical practice. Design/methodology/approach -A total of 58 registered midwives across two NHS Trusts in one region in the north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Following this, a further 5 were excluded; one explored midwives’ perceptions of the use of technology and was not explicitly about monitoring the FHR [15], one was a duplicate publication [16], one explored views on decision-making and was not explicitly about monitoring the FHR [17] and two were either non-comparable in design or it was impossible to extract themes from the data [18,19]. In total, 13 papers, detailing 11 studies (1,194 professionals), are included in our review (Figure 1); the findings of one study [20] are reported across two additional publications [21,22]. Details of the studies included are outlined in Table 1 and Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Following this, a further 5 were excluded; one explored midwives’ perceptions of the use of technology and was not explicitly about monitoring the FHR [15], one was a duplicate publication [16], one explored views on decision-making and was not explicitly about monitoring the FHR [17] and two were either non-comparable in design or it was impossible to extract themes from the data [18,19]. In total, 13 papers, detailing 11 studies (1,194 professionals), are included in our review (Figure 1); the findings of one study [20] are reported across two additional publications [21,22]. Details of the studies included are outlined in Table 1 and Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Reassurance emerged as a prominent theme in 9 [15,22-24,27-31] of the 11 included studies. EFM offered reassurance because professionals believed the cardiotocograph (CTG) trace provided hard copy ‘proof’ that the baby was not compromised whilst in their care [22-24,26,27,31].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations